Restructuring the Business Model of Smallholder Oil Palm Plantations in Forest Areas of Central Kalimantan Province: An Integration of Pestel-Porter Diagnostics and Social Forestry Solutions - Heru Hartako; Arman Nasution (International Journal of Science and Society, 2026)
This study aims to diagnose the vulnerability of the smallholder palm oil business model in the forest areas of Central Kalimantan Province and formulate its restructuring strategy through the Social Forestry policy. The land overlap issue covering 179,258 hectares places smallholders at high legal and economic risks following the enactment of the Job Creation Law (UU Cipta Kerja). The research method used is descriptive qualitative through an integrative approach using the Business Model Canvas (BMC), PESTEL, and Porter’s Five Forces frameworks. The diagnostic results reveal that the existing business model is highly vulnerable due to macro-regulatory constraints and the smallholders' weak bargaining power against informal markets. As a public governance solution, the Social Forestry policy through the Jangka Benah (transition period) scheme is capable of restructuring the elements of the smallholders' BMC blocks. This transformation alters the Key Resources aspect through long-term land utilization legality, improves Key Partnerships by eliminating middlemen, enhances the bargaining power of the product's Value Proposition, and realizes a sustainable, traceable, and legally compliant smallholder palm oil business model.